Development and application of thermal insulation material for underground roadway with high ground temperature. Issue 1 (31st December 2023) - Guan, Pinpin; Cheng, Jianwei; Zhu, Shuai; Zhang, Yongliang
ABSTRACT: Heat damage caused by high ground temperature is becoming a bottleneck restricting deep mining. The thermal insulation material is a heat damage prevention method that can effectively block the heat dissipation of the surrounding rock. The thermal insulation materials that have been developed so far cannot be well applied to deep mining practices with high stress and high ground temperature. Therefore, a foam fiber insulation material（thermal conductivity of 0.1164 W/(m·K), a compressive strength of 1.54 MPa） is developed in this paper. In addition, a similar physical simulation testing facility is used to analyze the application effect of thermal insulation materials. The results show that: (1) the thermal insulation material has an important effect on the heat dissipation of the surrounding rock and the dimensionless temperature and air flow temperature of the insulated roadway are much lower than those of the uninsulated roadway; (2) increasing the air velocity can effectively reduce the air flow temperature of the roadway.